Voxel-wise lesion mapping of self-reported urinary incontinence in multiple sclerosis - Fröhlich, Katharina; Wang, Ruihao; Bobinger, Tobias; Schmidt, Manuel; Dörfler, Arnd; Nickel, Franziska; Hilz, Max-Josef; Lee, De-Hyung; Linker, Ralf A.; Seifert, Frank; Winder, Klemens (Neurourology and Urodynamics, 2019)
Aims Besides spinal lesions, urinary incontinence may be attributed to particular cerebral lesion sites in multiple sclerosis (MS) patients. We intended to determine the contribution of suprapontine lesions to urinary incontinence in MS using a voxel-wise lesion analysis. Methods In this retrospective study, we sought MS patients with documented urinary incontinence in a local database. We established a control group of MS-patients without documented urinary incontinence matched for gender, age, and disease severity. Patients with urinary incontinence due to local diseases of the urinary tract were excluded. The MS lesions were analyzed on T2-weighted magnetic resonance imaging scans (1.5 or 3T). After manual delineation and transformation into stereotaxic space, we determined the lesion overlap and compared the presence or absence of urinary incontinence voxel-wise between patients with and without lesions in a given voxel performing the Liebermeister test with 4000 permutations. Results A total of 56 patients with urinary incontinence and MS fulfilled the criteria and were included. The analysis yielded associations between urinary incontinence and MS in the frontal white matter, temporo-occipital, and parahippocampal regions. Conclusions Our voxel-wise analysis indicated associations between self-reported urinary incontinence and lesions in the left frontal white matter and right parahippocampal region. Thus, our data suggest that dysfunction of supraspinal bladder control due to cerebral lesions may contribute to the pathophysiology of urinary incontinence in MS.
CRIS-Team WoS Importer:2019-11-12